Mineral and Anthropogenic Indicator Inorganics in Urban Stormwater and Snowmelt Runoff: Sources and Mobility Patterns - Galfi, H. (Water Air Soil Pollut, 2017)
Inorganic chemicals in urban stormwater and snowmelt runoff originate from catchment geology and anthropogenic activities. The occurrence, partitioning and mobility of six minerals and six trace metal (TM) indicators of anthropogenic activities were studied in stormwater, snowmelt and baseflow in four urban catchments, and the sampling of inorganics was supplemented by measurements of electrical conductivity (EC), pH and total suspended solids (TSSs). Minerals occurred at concentrations several orders of magnitude higher (1–10(2) mg/L) than those of TMs (10(−2)–10(2) μg/L) and reflected the composition of local groundwater seeping into sewers. Concentrations of Ca, K, Mg and Na were enhanced by baseflow contributions and followed closely the electrical conductivity. Al and Fe minerals occurred in insoluble forms, and their pollutographs were similar to those of TMs, whose concentrations mimicked, to some extent, the flux of TSS. The TMs with the highest and lowest particulate fractions were Cr&Pb and Cu&Zn, respectively. The concentrations of total TMs in snowmelt were two to four times higher than those in stormwater, and both sources likely exceeded some of the stormwater effluent limits (for Cd, Cu and Zn) proposed in Sweden. Where such concentrations depended on water hardness, the risk of toxicity might be reduced by elevated hardness of the monitored snowmelt and stormwater. Recognizing the good ecological status of the study area receiving water, Lake Storsjön, some protection against polluted runoff and snowmelt may be needed and could be achieved by implementing stormwater management measures controlling TSS and TMs.